2007
DOI: 10.1073/pnas.0611222104
|View full text |Cite
|
Sign up to set email alerts
|

ATM deficiency impairs thymocyte maturation because of defective resolution of T cell receptor α locus coding end breaks

Abstract: The ATM (ataxia telangiectasia mutated) protein plays a central role in sensing and responding to DNA double-strand breaks. Lymphoid cells are unique in undergoing physiologic doublestrand breaks in the processes of Ig class switch recombination and T or B cell receptor V(D)J recombination, and a role for ATM in these processes has been suggested by clinical observations in ataxia telangiectasia patients as well as in engineered mice with mutations in the Atm gene. We demonstrate here a defect in thymocyte mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
56
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 34 publications
11
56
2
Order By: Relevance
“…This is an autosomal recessive disorder characterized by progressive cerebellar degeneration and an increased incidence of cancer. Importantly, ATM deficiency leads to a defect in thymocyte maturation that is associated with decreased efficiency in V‐J rearrangement of the endogenous TCRα locus, accompanied by increased frequency of unresolved TCR‐Jα coding end breaks 55. It was also shown that residual ATM kinase activity correlates with the severity of immune defects 56…”
Section: Genes and Diseases Associated With Defective Recombination Imentioning
confidence: 99%
“…This is an autosomal recessive disorder characterized by progressive cerebellar degeneration and an increased incidence of cancer. Importantly, ATM deficiency leads to a defect in thymocyte maturation that is associated with decreased efficiency in V‐J rearrangement of the endogenous TCRα locus, accompanied by increased frequency of unresolved TCR‐Jα coding end breaks 55. It was also shown that residual ATM kinase activity correlates with the severity of immune defects 56…”
Section: Genes and Diseases Associated With Defective Recombination Imentioning
confidence: 99%
“…In this regard, deficiency in the ataxia telangiectasia mutated (ATM) serine threonine kinase in both mice and humans leads to an increased incidence of lymphoid tumors with RAG-dependent translocations involving antigen receptor loci (17)(18)(19)(20)(21). In addition, mature, nontransformed Atm-deficient lymphocytes have an increased frequency of translocations and other chromosomal aberrations involving antigen receptor loci (18,19,(22)(23)(24).…”
mentioning
confidence: 99%
“…Inhibition of the abl kinase with STI571 leads to G 1 cell cycle arrest, induction of RAG expression, and robust rearrangement of the endoge-nous Ig (Ig) light (L) chain genes and chromosomally integrated retroviral recombination substrates (25)(26)(27). Induction of V(D)J recombination by STI571 treatment of Atm Ϫ/Ϫ abl pre-B cells leads to an accumulation of un-repaired coding ends and to the aberrant resolution of these coding ends, analogous to what is observed in Atm-deficient lymphocytes in vivo (19,(22)(23)(24)(25). Here, we describe an experimental approach that permits high-throughput cloning of breakpoint targets from aberrantly resolved RAG DSBs generated during V(D)J recombination in Atm Ϫ/Ϫ abl pre-B cells.…”
mentioning
confidence: 99%
“…Other important aberrant translocations involving the Tcra/Tcrd locus include those that result in ataxia-telangiectasia mutations in the A-T mutated kinase (ATM) that cause chromosome instability and defects in DNA repair [69]. An important percent of A-T syndrome patients develop the disease due to translocations and inversions involving specific breakpoints at the Tcra/Tcrd locus and most of all ATM -/-mice die due to thymic lymphomas derived from and incorrect repair of the breaks that result from V(D)J recombination and aberrant Tcra/Tcrd locus translocations [70][71][72][73][74][75]. The knowledge of the precise mechanisms by which the Tcra/Tcrd locus transcription and recombination are regulated is important to understand the defective control of these processes that results in disease.…”
Section: Transcription and Recombinationmentioning
confidence: 99%